Determinants of The Entrepreneur's Performance of Graduates - Lubis, Delima Sari; Nasution, Hamni Fadlilah (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The aim of this researcher is to find out the factors that influence the entrepreneur's performance of graduates who choose business as a career. Is it due to socio-demographic factors (consisting of; age, gender, previous work, family background), attitudes (consisting of; autonomy/authority, economic challenges, self-realization, security and workload, avoid responsibility, social career, perceived behavioral control, subjective norms), contextual (consisting of; student participation in entrepreneurship education training, academic support, social support, environmental support, knowledge of entrepreneurship, independence of the entrepreneur). This research is quantitative research using primary data. The research results concluded that there were two factors that could be formed from the 15 variables analyzed. These factors are (1) Factor 1: Authority, Independence of the Entrepreneur, Social Support, Academic support, Entrepreneurship Training, Subjective Norms, Perceived Behavioral, Social Career, Avoid Responsibility, Security and Workload, Self-Realization, Economic Challenge. (2) factor 2, consisting of: Knowledge of Entrepreneurship, Environmental Support, Control, Perceived Behavioral